2015
DOI: 10.1007/s00436-015-4517-9
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Speed of Kill, Repellent (anti-feeding) and Acaricidal Efficacy of an Imidacloprid/Flumethrin Collar (Seresto®) and a Fipronil/(S)-Methoprene/Eprinomectin/Praziquantel Spot-on (Broadline®) against Ixodes ricinus (Linné, 1758) on Cats

Abstract: Speed of kill, repellent (anti-feeding) and acaricidal efficacy of an imidacloprid 10 % (w/w) /flumethrin 4.5 % (w/w) collar (Seresto ® , Bayer) and a spot-on formulation of fipronil 8.3 % (w/v) /(S)-methoprene 10 % (w/v) /eprinomectin 0.4 % (w/v) /praziquantel 8.3 % (w/v) (Broadline ® , Merial) against artificiallyinduced infestations with Ixodes ricinus on cats, were assessed in a parallel group design, randomised, controlled study. Twenty-four cats were included and randomly allocated to treatment groups or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 13 publications
0
9
0
Order By: Relevance
“…The toxicity of flumethrin was 8 times higher than that of coumaphos against ticks. Some studies have shown that 1% flumethrin pour-on has 95-100% lethality for ectoparasites (17). Flumethrin can prevent disease transmission by ticks, fleas, mites and other ectoparasites due to its repellent property (preventing blood feeding) (17).…”
Section: Discussionmentioning
confidence: 99%
“…The toxicity of flumethrin was 8 times higher than that of coumaphos against ticks. Some studies have shown that 1% flumethrin pour-on has 95-100% lethality for ectoparasites (17). Flumethrin can prevent disease transmission by ticks, fleas, mites and other ectoparasites due to its repellent property (preventing blood feeding) (17).…”
Section: Discussionmentioning
confidence: 99%
“…For example, a recent study has shown vapors of metofluthrin and d ‐allethrin, which is a non‐fluorinated pyrethroid, both repelled and killed ticks . Conversely, flumethrin is a pyrethroid that is used primarily to repel or kill ticks on domestic animals . This pyrethroid has not been tested against mosquitoes, but flumethrin has been demonstrated to repel and kill Sand flies in the genus Phlebotomus Loew…”
Section: Introductionmentioning
confidence: 99%
“…The mortality recorded in prior studies is consistent, but measurements were performed in environments with limited control of exposure or in a way that did not exclude mosquitoes from physical contact with the compound . Mortality focused studies also have not attempted to characterize the range of outcomes on a dose response curve .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations